2018
DOI: 10.1097/scs.0000000000004584
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Cicatricial Entropion With Labial Mucous Membrane Graft in Cicatricial Ocular Surface Disorders

Abstract: The management of cicatricial entropion represents a therapeutic challenge especially when the underlying causes are progressive cicatricial diseases that affect the ocular surface. The authors aimed to report long-term efficacy of labial mucous membrane graft to manage severe cicatricial entropion of the upper eyelid. This study is a retrospective chart review of patients who underwent tarsotomy associated with labial mucous membrane graft to treat severe cicatricial entropion of the upper eyelid. Surgeries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, with the progression of the cicatricial process, a more definitive procedure might be needed to decrease the recurrence rate. 2,7 In our study, the underlying cicatricial process in the patients was controlled and was at an end-stage. The combined surgical strategies described herein were straightforward to correct abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the progression of the cicatricial process, a more definitive procedure might be needed to decrease the recurrence rate. 2,7 In our study, the underlying cicatricial process in the patients was controlled and was at an end-stage. The combined surgical strategies described herein were straightforward to correct abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…U pper eyelid cicatricial entropion and trichiasis are difficult to manage. [1][2][3] Tarsoconjunctival scarring causes shrinkage of the posterior lamellar and inward malrotation of the lid margin. [4][5][6] Moreover, it might cause rounding of the posterior lid border, posterior migration of the keratinized epithelium, and secondary trichiasis.…”
mentioning
confidence: 99%
“…Sadiq et al reported bilamellar tarsal margin rotation with blepharoplasty to address the UCE (11). Osaki et al combined labial mucous membrane grafts to lengthen the posterior lamella to treat severe UCE (7). Besides all of the above, there are some other new surgical method for Caucasian trachomatous UCE, such as anterior lamellar reposition and tarsal margin rotation with posterior lamella superadvancement (6,12).…”
Section: Discussionmentioning
confidence: 99%
“…The definitive treatment for trachoma-induced UCE is surgery. Surgeons have developed various surgical techniques to address UCE, including tarsotomy with margin rotation (6), posterior lamella lengthening using grafts (7), eyelash resection (8), and anterior lamella recession (9). But due to the special anatomical characteristics, the single surgery isn't suitable for Chinese…”
Section: Introductionmentioning
confidence: 99%
“…The authors report data from a 16-year period, and quoted a 98% improvement in ocular symptoms, an 83% rate of complete restoration of normal upper eyelid position, and an 11% recurrence rate. 20 Additionally, in line with the overwhelming trend towards minimally invasive surgery over the last decade, a grey-line-incision-only approach to anterior lamella repositioning has been proposed. This technique avoids the classic skin-crease or conjunctival incisions, and reported a 100% success rate in achieving a normal lid margin, and 72% of patients reporting symptomatic improvement.…”
Section: Cicatricial Entropionmentioning
confidence: 99%